Contraception and the Demographic Transition. (24th May 2017) - Bhattacharya, Joydeep; Chakraborty, Shankha
Abstract : Inspired by the historical English experience, we modify the Beckerian paradigm of fertility by incorporating costly, societal influence on contraception. Heterogeneous, generationally‐linked households choose between 'traditional' and 'modern' contraception. The modern has a higher fixed but lower variable cost of averting childbirths. Initially the rich adopt the modern, which unleashes society‐wide diffusion. Eventually everyone switches, lowering fertility further and across households. Hastening the switch is falling child mortality. Quantitative experiments suggest contraception was a vital link between the historical mortality and fertility transitions, though not the latter's proximate cause. Implications for more recent transitions are discussed.